Analysis of Local Wisdom Values in the Seumapa Tradition in Society in Bireuen Regency - Fina Meilinar; Alfi Syahrin; Cut Khairani (Edumaspul: Jurnal Pendidikan, 2023)
The purpose of this study is to analyze the values of local wisdom and the implementation of the Seumapa tradition. This study uses a qualitative descriptive method, data collection techniques using the stages of observation, interviews and documentation with the aim of studying the values of local wisdom in the seumapa tradition in the people of Bireuen Regency. The results of the study found that there are local wisdom values in the art of saying seumapa, namely the value of welfare and prosperity which consists of the values of hard work, discipline, education, health, mutual cooperation, gender management, preservation, cultural creativity, care for the environment, and values of peace or justice, consisting of politeness, honesty, social solidarity, harmony (conflict resolution), commitment, positive thinking, gratitude, gratitude to the divine. The local wisdom values contained in the seumapa tradition have been implemented in the daily life of the Acehnese people, especially in Bireuen District. This can be seen from glorifying the guests who attend our residence along with events at party receptions, where when going to the wedding party house and the funeral home, the whole village community will visit the party or funeral houses in their village and in neighboring villages. As long as it becomes an art of speech that has local Acehnese wisdom values that are in accordance with Aqidah and muamalah in accordance with the teachings of the Islamic Religion adhered to by the people of Aceh, especially Bireuen Regency.